Creativity: Intrapersonal and Interpersonal Selection of Creative Ideas. (13th January 2019) - Zhu, Yuxi; Ritter, Simone M.; Dijksterhuis, Ap
Abstract: Creative idea selection—the selection of the most creative idea(s) from available ideas—is an important yet understudied topic. Creative idea selection can be performed by the idea generator (i.e., intrapersonal selection) or by another person (i.e., interpersonal selection). In the current research, we examined whether these two types of selection lead to different levels of performance. Participants generated six creative ideas to solve a societal problem. Thereafter, two selection tasks—intrapersonal selection and interpersonal selection—were performed. During intrapersonal selection, the idea generator selected the most creative idea from his/her own ideas; during interpersonal selection, another person made the selection from the same ideas. We found no effect of intrapersonal and interpersonal selection on creative idea selection performance: People selected ideas of identical creativity, irrespective of whether that idea was from themselves or from others. Moreover, we replicated the earlier finding that people perform suboptimally at creative idea selection, failing to select ideas that were more creative than an average idea, for both intrapersonal and interpersonal selection.